Fungal Endophytes of Tahiti Lime (Citrus citrus × latifolia) and Their Potential for Control of Colletotrichum acutatum J. H. Simmonds Causing Anthracnose - Muñoz-Guerrero, Jaider; Guerra-Sierra, Beatriz E.; Alvarez, Javier C. (Frontiers in Bioengineering and Biotechnology, 2021)
Colletotrichum acutatum is one of the causal agents of anthracnose in several crops, and of post-flowering fruit drop (PFD) in citrus and key lime anthracnose (KLA). The pathogen normally attacks flowers, causing lesions only in open flowers. Under very favorable conditions, however, it can also affect flower buds and small fruits, causing complete rotting of the fruit and a premature fall, resulting in major economic crop losses. We isolated endophytic fungi from Tahiti lime to evaluate its diversity, verify its antagonistic capacity against the phytopathogen Colletotrichum acutatum C-100 in dual tests, and evaluate the ability of various endophytic agents to control flowers with induced anthracnose. 138 fungal isolates were obtained from 486 fragments of branches, leaves, and fruit; from which 15 species were identified morphologically. A higher isolation frequency was found in branches and leaves, with a normal level of diversity compared to other citrus species. Of the 15 morphospecies, 5 were trialed against C. acutatum in antagonism tests, resulting in a finding of positive inhibition. 2 endophytic fungi from the antagonism tests demonstrated high inhibition of the phytopathogen, and were thus used in in vivo tests with Tahiti lime flowers, applied in a spore solution. Spore solutions of two molecularly identified species, Xylaria adscendens, and Trichoderma atroviride, reduced the lesions caused by the phytopathogen in these in vivo tests. The finding that these endophytes react antagonistically against C. acutatum may make them good candidates for further biological control research in an agro-industry that requires environmental sustainability.